Leading from the Frontlines: School Principals' Perspectives on Crisis Management during the New Normal - Irmalyn Borja Paymalan; Maria Shayne Borja Budias (Universitas Ahmad Dahlan, 2023)
The present study investigated the emergence of situational leadership during COVID-19 pandemic called new normal leadership among secondary school principals of Taganaan District, DepED-Surigao del Norte Division. Based on the criterion, all the five full-fledged secondary school principals in the district during the school year 2020-2021are the participants. The study employed Colazziâ€™s descriptive phenomenological approach. Using transcriptions, codes, and triangulations of the data gathered, themes were extracted in the data analysis. Findings revealed that: (1) New Normal leadership is the ability to be persuasive and proactive in their efforts while securing the protection and safety of their constituents; (2) It is being flexible and adaptive but adherent with oneâ€™s resposiblities and undertakings; (3) It is about being an an effective instructional decision-maker; (4) A leader who is selfless, compassionate, and resilient in solidifying its commitment. Indeed, school principal honestly demonstrated New Normal Leadership in this challenging condition to sustainÂ the nation's quality education.